Estrategias para el fortalecimiento de las competencias ciudadanas en escenarios virtual de aprendizaje en la Institución Educativa Concentración Cevillar (2015)
The current context offers to the education the possibility of generating new stages to carry out processes of formation and investigation by means of the integration of the TIC. The Project arises like answer to the opportunities that offers the implementation of Virtual Stages of Learning (EVA) as facilitating factor for the strengthening of the civil competitions in students of the grade 11 of basic average. In this sense the present investigation thinks about how to design strategies that allow to strengthen the civil competitions in one EVA in order to inject progress to the learning processes and simultaneously to allow to the teachers to offer an education of quality rested on the TIC. The investigation corresponds to a transactional field work, descriptively and, of not experimental design; which capture as skill of compilation of the information the direct observation without manipulating deliberately the variables, being based on such theories like Theory of the educational psychology and social psychology, applied completely to the educational context. EVA sees the impact of this project reflected in the construction of one by means of which there is promoted the development and strengthening of the civil competitions from an integral and exact perspective to the social reality of the students